Optimism and resilience: the Golden Path to sportive performance? - Estefanía Malán-Ernst; Julio Imbernón de Álvaro; Regina Brandão; Mario Alexander Reyes-Bossio; Hernán Pereira; Mariel Delgado-Campusano; Francisco Ortín-Montero; Alejandro García-Mas; Verónica Tutte-Vallarino (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: the importance of the study lies in understanding the relevance of burnout as a detriment to the quality of life and performance of high performance athletes.